2005
DOI: 10.1590/s0066-782x2005000500012
|View full text |Cite
|
Sign up to set email alerts
|

Tendência temporal de letalidade hospitalar por infarto agudo do miocárdio: 1994-2003

Abstract: There was a decrease in lethality and the change of behavior in the treatment of AMI along the years was responsible for the reduction of lethality in that temporal series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
3
1
0
Order By: Relevance
“…The mortality and morbidity from AMI depends on factors related to the severity of the disease and the speed and quality of hospital care. If the patient receives appropriate hospital care within few hours after onset of the symptoms, the mortality worldwide is around 10% 2, similar to that observed in the hospitals of the cities of Rio de Janeiro (10.8%) and Niterói (12.3%) 3,4 . However, this percentage may not reflect the reality when there are factors such as delay between the onset of pain and arrival at the hospital, delay in the start of in-hospital treatment, restrictions on the use of myocardial protection measures, such as primary angioplasty and thrombolytics, and on access to intensive care unit 2,5 .…”
supporting
confidence: 58%
“…The mortality and morbidity from AMI depends on factors related to the severity of the disease and the speed and quality of hospital care. If the patient receives appropriate hospital care within few hours after onset of the symptoms, the mortality worldwide is around 10% 2, similar to that observed in the hospitals of the cities of Rio de Janeiro (10.8%) and Niterói (12.3%) 3,4 . However, this percentage may not reflect the reality when there are factors such as delay between the onset of pain and arrival at the hospital, delay in the start of in-hospital treatment, restrictions on the use of myocardial protection measures, such as primary angioplasty and thrombolytics, and on access to intensive care unit 2,5 .…”
supporting
confidence: 58%
“…The in-hospital mortality rate among unselected patients with AMI ranged from 10 to 20% 18 . The mortality rate of 17.5% found in this sample was similar to that found in other Brazilian [4][5][6]19 and international studies (12.6%) 10 . These values are quite different from the value of 6.1% found in randomized clinical trials, such as the TIMI study 9 .…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of elevated blood pressure (61.2%) was similar to that found in Brazilian studies [4][5][6]15 and higher than that found in international studies (21.6% 9 and 54% 10 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation